Analisis Kesulitan Membaca Anak Disleksia Kelas II SD Negeri Ciceri Indah - Adah; Fauzi Fadliansyah; Miftah Komala Putri (Arden Jaya Publisher, 2025)
This study aims to analyze the reading difficulties experienced by students with dyslexia and to identify the efforts made by teachers to overcome these challenges in Grade II at SD Negeri Ciceri Indah. The background of this research is based on findings that some students with dyslexic symptoms show significant obstacles in recognizing letters, sequencing letters in words, distinguishing similar letters, and maintaining reading consistency across lines. This research employs a qualitative approach with a case study method. Data were collected through participatory observation, in-depth interviews with teachers and parents, as well as documentation. The results indicate that the reading difficulties experienced by students include: (1) errors in letter recognition such as reading “b” as “d” or “m” as “w”; (2) difficulties in sequencing letters within words; (3) inconsistency in reading; and (4) low comprehension of reading content. The efforts made by teachers to address these difficulties include individual approaches, the use of visual.